Antimicrobial Properties of the Ag, Cu Nanoparticle System - Xinzhen Fan (Biology, 2021)
Microbes, including bacteria and fungi, easily form stable biofilms on many surfaces. Such biofilms have high resistance to antibiotics, and cause nosocomial and postoperative infections. The antimicrobial and antiviral behaviors of Ag and Cu nanoparticles (NPs) are well known, and possible mechanisms for their actions, such as released ions, reactive oxygen species (ROS), contact killing, the immunostimulatory effect, and others have been proposed. Ag and Cu NPs, and their derivative NPs, have different antimicrobial capacities and cytotoxicities. Factors, such as size, shape and surface treatment, influence their antimicrobial activities. The biomedical application of antimicrobial Ag and Cu NPs involves coating onto substrates, including textiles, polymers, ceramics, and metals. Because Ag and Cu are immiscible, synthetic AgCu nanoalloys have different microstructures, which impact their antimicrobial effects. When mixed, the combination of Ag and Cu NPs act synergistically, offering substantially enhanced antimicrobial behavior. However, when alloyed in Ag–Cu NPs, the antimicrobial behavior is even more enhanced. The reason for this enhancement is unclear. Here, we discuss these results and the possible behavior mechanisms that underlie them.